Shareholders' versus management's interest: A review - Mohamad, Shamsher; Md. Nassir, Annuar (Universiti Utara Malaysia, 1992)
Shareholders are basically owners of their corporations who elect corporate directors (who are policy makers) and employed corporate management (who implement corporate policies). In modern businesses, due to the large number and dispersion of shareholders, control is normally vested to professional managers who may pursue actions in their own self-interest rather than those of the shareholders. This paper reviews various ways managers are perceived to deviate from the shareholders' wealth maximisation objective, and the possible methods and constraints involved of aligning management's and shareholders'interest.